Peningkatan Kemampuan Operasional Penjumlahan Dan Pengurugan Siswa Dengan Benda Kongkrit - Erna Sugiarti; Ahmad Yulianto (Jurnal Sultra Elementary School, 2023)
This study aims to improve students' abilities in operationalizing addition and subtraction with the help of concrete objects. To achieve this goal, a classroom action research was conducted on 20 first-grade students of SD Inpres 28 Sorong Regency. The data obtained in this study were through observation, discussion, and evaluation. The results of this study showed an increase in pre-action activities, cycle I, and cycle II. In the pre-action research, 33.3% of students experienced learning completion after the action was carried out with concrete objects as aids. Student learning completion in cycle I increased to 66.6%, followed by the next cycle where all students experienced learning completion. Based on the results of the learning evaluation in cycle I with the lowest standard score of 75, students who obtained a score of 75 were 33.3% of students or approximately 97% while the results of the evaluation in cycle II with the same standard score, all students obtained a score of 75 or 100. The conclusion that can be drawn is that concrete objects can help students in operationalizing addition and subtraction of numbers in Class I Mathematics learning, so that learning achievement has progressed. Other findings are that students become happy, confident in carrying out the learning process that uses concrete objects. By using concrete objects, it can improve students' abilities in operating addition and subtraction.